2012
DOI: 10.1016/j.yjmcc.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and evaluating the role of ATP-sensitive K+ channels in cardiac muscle

Abstract: Since ion channels move electrical charge during their activity, they have traditionally been studied using electrophysiological approaches. This was sometimes combined with mathematical models, for example with the description of the ionic mechanisms underlying the initiation and propagation of action potentials in the squid giant axon by Hodgkin and Huxley. The methods for studying ion channels also have strong roots in protein chemistry (limited proteolysis, the use of antibodies, etc). The advent of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 130 publications
(157 reference statements)
0
7
0
3
Order By: Relevance
“…The shortening of the action potential duration following a decline in oxygen support has been attributed to the opening of ATP-sensitive potassium channels. [8][9][10][11][12] We reported that the hypoxia-induced decline in action potential duration of the adult guinea pig ventricular myocardium was partially attenuated by the ATP-sensitive potassium channel blocker, glybenclamide. 13) Thus it was possible that the resistance of guinea pig fetal myocardium to hypoxia was due to a lack of the ATP-sensitive potassium channel.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The shortening of the action potential duration following a decline in oxygen support has been attributed to the opening of ATP-sensitive potassium channels. [8][9][10][11][12] We reported that the hypoxia-induced decline in action potential duration of the adult guinea pig ventricular myocardium was partially attenuated by the ATP-sensitive potassium channel blocker, glybenclamide. 13) Thus it was possible that the resistance of guinea pig fetal myocardium to hypoxia was due to a lack of the ATP-sensitive potassium channel.…”
Section: Discussionmentioning
confidence: 98%
“…7) The ATP-sensitive potassium channel is present in cardiomyocytes and is activated under hypoxic conditions and by pharmacological agents. [8][9][10][11][12] The ATP-sensitive potassium channel current (I KATP ) has a linear voltage dependence and thus generates a potent repolarizing power at depolarized membrane potentials. I KATP is responsible for the hypoxiainduced shortening of the myocardial action potential and decrease in contraction.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Bu bilgi çinkonun KATP'nin di¤er alt birimi olan SUR üzerinden kanal aktivitesini etkileyebilece¤ini düündürmektedir. Dahası SUR alt biriminin dahil oldu¤u ABC ailesi proteinlerinden [26] bazı üyeler Zn +2 taıyabilmektedir. [15] Dolayısıyla Zn +2 SUR'un bir substratı olarak kullanılıyor olabilir.…”
unclassified
“…[15] Bu öngörümüz 2009 yılında yayınlanmı bir çalıma ile desteklenmektedir. [27] Bu çalımada, SUR1 insülin granüllerin ekzositozunda da önemli rol oynadı¤ı belirtilmitir. KATP kanalları hücre membranında çok, insülin granüllerinde daha çok bulunmaktadır.…”
unclassified
See 1 more Smart Citation